2022
DOI: 10.1038/s41598-021-04241-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased climate pressure on the agricultural frontier in the Eastern Amazonia–Cerrado transition zone

Abstract: Several large-scale drivers of both anthropogenic and natural environmental changes are interacting nonlinearly in the transition zone between eastern Amazonia and the adjacent Cerrado, considered to be another Brazilian agricultural frontier. Land-use change for agrobusiness expansion together with climate change in the transition zone between eastern Amazonia and the adjacent Cerrado may have induced a worsening of severe drought conditions over the last decade. Here we show that the largest warming and dryi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
41
0
19

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 66 publications
11
41
0
19
Order By: Relevance
“…The SDG indicator 15.3.1 revealed several land degradation hotspots in the Amazon basin between 2001 and 2020, most of which were located in the Brazilian states of Pará, Mato Grosso, Amazonas, and Rondônia. This result ties well with previous studies wherein such land degradation hotspots were identified (Anderson et al, 2018;Arima et al, 2021;Marengo et al, 2022).…”
Section: Long-term Land Degradation In the Amazon Basinsupporting
confidence: 92%
See 1 more Smart Citation
“…The SDG indicator 15.3.1 revealed several land degradation hotspots in the Amazon basin between 2001 and 2020, most of which were located in the Brazilian states of Pará, Mato Grosso, Amazonas, and Rondônia. This result ties well with previous studies wherein such land degradation hotspots were identified (Anderson et al, 2018;Arima et al, 2021;Marengo et al, 2022).…”
Section: Long-term Land Degradation In the Amazon Basinsupporting
confidence: 92%
“…Usually, this would lead to short-term declines in rainfed crop yields and progressive land degradation (Sims et al, 2019). This assumption is supported by recent studies highlighting the impacts of large monocultures and fragmented landscapes on biodiversity in the southwestern Amazon basin (de Almeida et al, 2020;Marengo et al, 2022).…”
Section: Long-term Land Degradation In the Amazon Basinmentioning
confidence: 82%
“…These human conditions, together with climate change, were the basis for developing impact projections of the erosivity of rains in the AW region, alerting to possible scenarios of soil erosion (Santos et al, 2022). According to Marengo et al (2022), the transition zone between the Amazon and Cerrado biomes is marked by strong pressures from agricultural frontiers, and in the face of climate change, such adverse conditions cause a delay in the rainy season, decreased precipitation, humidity and evapotranspiration, and an increase in dry days.…”
Section: La Niñamentioning
confidence: 99%
“…MATOPIBA presents, at the same time, the largest undisturbed remnants of Cerrado vegetation and a quarter of the Cerrado soybean area [21,23], equally important for environmental and economic issues, respectively. Nonetheless, over the last decade, the combination of climate change and land-use change has severely increased drought conditions in the region, which contribute to a higher fire risk, mainly during the fire season [24], and jeopardize biodiversity and food security.…”
Section: Introductionmentioning
confidence: 99%